Collection and processing of a Medical Corpus in Ukrainian - Cherednichenko, Olga; Kanishcheva, Olga; Yakovleva, Olena; Arkatov, Denis (My University, 2020)
The text corpora are the basis of natural language studying. We describe the structure of a Ukrainian-language corpus (UKRMED), which contains a variety of medical text genres (Сlinical protocols, Blogs, and Wikipedia). The paper shows the process of collecting, creating and processing a corpus of medical data in Ukrainian. We represent our own framework for creating a text corpus. The medical domain and text simplification are chosen as corpus directions. The authors gave statistical characteristics of the corpus, an analysis of the morphological parts of speech is provided. Frequency lemmas for this medical corps are analyzed. The UKRMED corpus can be used for solving the task of natural language simplification.
Keywords: Medicine Corpus; Corpus Linguistic; Ukrainian; Text Collection; Ukrainian-language corpus; Natural Language Processing